2018
DOI: 10.15386/cjmed-1042
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of 131I radioprotection measures on thyroid cancer patients

Abstract: Background and aimsIt is very well know nowadays that despite all the good and qualitative information available, the patients who are supposed to be treated with radioiodine for differentiated thyroid cancer suffer from a lot of concerns prior the treatment. The aim of our study is to investigate the level of anxiety and lessening of the concerns pre and post RIT (radioiodine therapy) using a dedicated, special designed questionnaire.MethodsA cross-sectional study of 54 differentiated thyroid cancer patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Our study supported some protective factors associated with increased QoL, which include good communication between the patient and the healthcare team via adequate and accurate information-giving, which can decrease patients’ anxiety levels and improve their QoL [ 79 ]. Psychological and behavioral interventions were also shown to improve QoL and reduce depression and anxiety [ 80 , 81 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our study supported some protective factors associated with increased QoL, which include good communication between the patient and the healthcare team via adequate and accurate information-giving, which can decrease patients’ anxiety levels and improve their QoL [ 79 ]. Psychological and behavioral interventions were also shown to improve QoL and reduce depression and anxiety [ 80 , 81 ].…”
Section: Discussionsupporting
confidence: 66%
“…The association between protective factors and anxiety, depression, or QoL in TC has been reported in 3 studies ( Table 4 ) [ 79 - 81 ]. One prospective study [ 79 ] established that patients who received more dedicated time for information-giving were less anxious about the treatment and concluded that good communication between the patient and the medical team is associated with increased QoL. A randomized control trial by Wang et al .…”
Section: Resultsmentioning
confidence: 99%
“…The potential toxicities of RIA were highlighted, as the increased risk of sialadenitis and reduced swallowing capability negatively affected HRQOL. 55 Despite >50% of patients having anxiety and concerns prior to RIA, Barbus et al 56 found most patients would undergo further courses if indicated, suggesting treatment burden has a relatively low HRQOL effect. This was supported by Taïeb et al, 50 who reported RIA to have no significant effect on HRQOL in the medium term (9 months).…”
Section: Resultsmentioning
confidence: 99%
“…The differences in HRQoL among total thyroidectomy, lobectomy, and robot-associated thyroidectomy remain inconclusive [5,[28][29][30]. The risk of sialadenitis and dysphagia after RAI, anxiety before RAI, iatrogenic hypothyroidism, and hyponatremia during a low-iodine diet with thyroid hormone withdrawal were associated with low HRQoL [11,[31][32][33]. In contrast to thyroid hormone withdrawal, preparation for RAI therapy with recombinant TSH was positively correlated with HRQoL [5,34,35].…”
Section: Discussionmentioning
confidence: 99%